Posttranslational Regulation of Nitrate Assimilation in the Cyanobacterium Synechocystis sp. Strain PCC 6803 - Kobayashi, Masaki (American Society for Microbiology, 2005)
Posttranslational regulation of nitrate assimilation was studied in the cyanobacterium Synechocystis sp. strain PCC 6803. The ABC-type nitrate and nitrite bispecific transporter encoded by the nrtABCD genes was completely inhibited by ammonium as in Synechococcus elongatus strain PCC 7942. Nitrate reductase was insensitive to ammonium, while it is inhibited in the Synechococcus strain. Nitrite reductase was also insensitive to ammonium. The inhibition of nitrate and nitrite transport required the P(II) protein (glnB gene product) and the C-terminal domain of NrtC, one of the two ATP-binding subunits of the transporter, as in the Synechococcus strain. Mutants expressing the P(II) derivatives in which Ala or Glu is substituted for the conserved Ser(49), which has been shown to be the phosphorylation site in the Synechococcus strain, showed ammonium-promoted inhibition of nitrate uptake like that of the wild-type strain. The S49A and S49E substitutions in GlnB did not affect the regulation of the nitrate and nitrite transporter in Synechococcus either. These results indicated that the presence or absence of negative electric charge at the 49th position does not affect the activity of the P(II) protein to regulate the cyanobacterial ABC-type nitrate and nitrite transporter according to the cellular nitrogen status. This finding suggested that the permanent inhibition of nitrate assimilation by an S49A derivative of P(II), as was previously reported for Synechococcus elongatus strain PCC 7942, is likely to have resulted from inhibition of nitrate reductase rather than the nitrate and nitrite transporter.